The effect of pneumovesicoscopic Cohen surgery using a segmented submucosal tunnel and reduced intra-abdominal pressure for the treatment of vesicoureteral reflux in children - Chen, Hong; Cui, Xu; Zhou, Chaoming; Zhang, Jianqin; Chen, Liu (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to explore the effect of using a segmented submucosal tunnel and reducing intra-abdominal pressure in the treatment of CO2 leaking from the bladder into the abdominal cavity in vesicoureteral reflux (VUR) patients during pneumovesicoscopic Cohen surgery.MethodA retrospective analysis was conducted on children aged 0–1 years with VUR who underwent pneumovesicoscopic Cohen surgery at the Department of Urology, Fujian Children's Hospital from 1 May 2021 to 1 October 2024. Among them, 56 cases had CO2 leakage from the bladder into the abdominal cavity during the surgery. The patients were divided into two groups based on the surgical method: Group A, 28 cases, where a submucosal tunnel was directly established during surgery, and Group B, 28 cases, where a submucosal tunnel was established in segments and decompression of the abdominal cavity was performed during surgery. Intraoperative and postoperative outcomes, complications, and clinical efficacy were compared between the two groups.ResultsNo complications from bladder leakage, anastomotic stenosis, or urinary retention occurred in either group after surgery, and no reoperations were necessary. In Group A, two cases were converted to open surgery, while no conversions were necessary in Group B. No statistically significant difference was found in indicators such as placement of the ureteral catheter, pain score (6 h after surgery), postoperative hospitalization time, conversion to open reimplantation, postoperative UTI, postoperative VUR, and postoperative hematuria time. The operation time (187.11 ± 55.29 min vs. 157.79 ± 44.96 min, P < 0.05) and pain score 2 h after surgery (2.21 ± 0.79 vs. 1.39 ± 0.99, P < 0.05) in Group B were lower than those in Group A.ConclusionReducing intra-abdominal pressure combined with segmental submucosal tunneling is a simple, safe, and effective approach, which is recommended for managing CO2 leakage from the bladder into the abdominal cavity of VUR patients during pneumovesicoscopic Cohen surgery.